Using Ive-Snap card game to improve year 4 students’ memorisation of past simple irregular verbs / Sudipa Chakraverty ... [et al.] - Chakraverty, Sudipa; Sim, Hannah Phek-Khiok; Chung-Wei, Kho; Sandra, Phek-Lin Sim (Universiti Teknologi MARA, Kedah, 2024)
The use of language games in grammar lessons to engage students is gaining popularity instead of using traditional teaching techniques to teach grammar. This action research sets out to investigate how using the Ive-Snap card game could help Year 4 students use simple past tense irregular verbs more effectively. The data collection methods used in this research included pre- test, post-test, interviews and observation. Eight Year 4 students with varying levels of English language proficiency played the card game. The students were interviewed before and after the implementation of the intervention to share their responses regarding the Ive-Snap card game. They first took a pre-test before the card game was introduced, then subsequently sat for two post-tests — one after each cycle of the intervention. The data were analysed using descriptive statistics and reported accordingly. The results demonstrated that the Ive-Snap card game successfully enhanced students' use of past simple irregular verbs because it maintained their interest in learning. Results also showed that Ive-Snap card game is an effective pedagogical approach in engaging participants in fun learning of grammar and increasing their mastery of irregular verbs. As a result, the study shows how language games can be used as an approach for facilitating ESL learners' grammar acquisition and creating a relevant context for language learning.